Keterlibatan Mahasiswa dan Akademisi dalam Pengabdian Masyarakat Menghadapi Pandemi Covid-19 - Seri Hartati; Amir Syamsuadi; Luluk Elvitaria (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Coronavirus (COVID-19) is an infectious disease caused by a new version of the coronavirus that was discovered at the end of 2019. Most of the disorders experienced by individuals infected with the COVID-19 virus will experience respiratory disease and most of them recover without requiring special treatment. Indonesia is currently hit by the Covid-19 pandemic. Various policies in prevention efforts have been carried out by the government, which have an impact many aspects of society. In Pekanbaru specially needs a lot of information related to Covid 19. Through Community Service in Simpang Tiga Village, Bukit Raya District, they can provide aid of information or other social aid which is a synergy of students and academics during the Covid 19 Pandemic, of course by following health protocol procedures. The results of this service are expected to assist the government and society as an effort to break the chain of spreading covid-19.